Катрин в замке смерти: роман / Жюльетта Бенцони - Бенцони Жюльетта (Семейный роман, 1993)
Экземпляры: ф.6 (2003) / Инвентарный номер: 45141 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: Б 46 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44